2004
DOI: 10.1002/ejoc.200400289
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Redox Behavior of Wurster Blue Cyclophanes

Abstract: Two cyclophanes composed of two p‐phenylenediamine (PPD) units connected by methylene chains of different lengths (1c, n = 3; 2c, n = 5) have been synthesized. The PPD unit of cyclophane 1c was oxidized by a two‐electron transfer process to give 1c2+ at the first oxidation potential. In contrast, 2c was oxidized by a one‐electron transfer process to give 2c+ and then 2c2+. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…These two redox processes for 1 – 3 would correspond to the stepwise ligand‐centered oxidation of each of the two facing polymethyl‐substituted para‐ phenylenediamidate bridges. Hence, the resulting dicopper(II)/π radical and diradical species are the metallacyclic analogues of forms I and II from the N , N ′, N ′′, N ′′′‐tetramethyltetraza[7.7]paracyclophane, which shows similar values of the formal potentials to those of 3 ( E 1 =+0.08 and E 2 =+0.69 V vs. SCE) 6a. The observed linear decrease of the E 1 values according to 1 > 2 > 3 indicates that the oxidation of the polymethyl‐substituted para ‐phenylenediamidate bridge is favored as the number of electron‐donating methyl substituents increases (Figure 5).…”
Section: Resultsmentioning
confidence: 96%
“…These two redox processes for 1 – 3 would correspond to the stepwise ligand‐centered oxidation of each of the two facing polymethyl‐substituted para‐ phenylenediamidate bridges. Hence, the resulting dicopper(II)/π radical and diradical species are the metallacyclic analogues of forms I and II from the N , N ′, N ′′, N ′′′‐tetramethyltetraza[7.7]paracyclophane, which shows similar values of the formal potentials to those of 3 ( E 1 =+0.08 and E 2 =+0.69 V vs. SCE) 6a. The observed linear decrease of the E 1 values according to 1 > 2 > 3 indicates that the oxidation of the polymethyl‐substituted para ‐phenylenediamidate bridge is favored as the number of electron‐donating methyl substituents increases (Figure 5).…”
Section: Resultsmentioning
confidence: 96%
“…This paper reports on oxidized Me3C , Et3C , and iPr3C , which have been studied as both radical cations and diradical dications. Oxidation of Me3C and Me5C was studied earlier by Takemura and co-workers . They concluded that Me3C + could not be obtained and found that Me3C 2+ is diamagnetic but Me5C 2+ is paramagnetic.…”
mentioning
confidence: 96%
“…Although produced oxidatively, most of the diamines 1a-h prepared in this work were sensitive to oxidation. 9,13 This was not surprising in view of the applications for diamines 1a-h as antioxidants and it implied the need for careful work-up to minimise discrepancies between conversions and isolated yields. When necessary, to limit the extent of decomposition, products were isolated as their dihydrochloride salts from organic solutions of the diamines 1a-h, which mainly were low melting point solids.…”
Section: Resultsmentioning
confidence: 99%
“…p-Phenylenediamines (1) are useful stabilisers for polymers, particularly as antioxidants and antiozonants for rubbers. 4 They also serve as synthetic starting materials for flavins, 5 bis-Tro ¨ger's bases, 6 rod-like oligomers, rotaxanes, 7 redox-active macrocycles [8][9][10] and ladder polymers. 11 Published routes to 1 often involve multiple steps, [11][12][13][14][15][16][17] including protection and deprotection, that introduce two additional manipulations and lower the atom economy.…”
Section: Introductionmentioning
confidence: 99%